2023
DOI: 10.1172/jci.insight.145688
|View full text |Cite
|
Sign up to set email alerts
|

Reduced G protein signaling despite impaired internalization and β-arrestin recruitment in patients carrying a CXCR4Leu317fsX3 mutation causing WHIM syndrome

Abstract: WHIM syndrome is an inherited immune disorder caused by an autosomal dominant heterozygous mutation in CXCR4. The disease is characterized by neutropenia/leukopenia (secondary to retention of mature neutrophils in bone marrow), recurrent bacterial infections, treatment-refractory warts, and hypogammaglobulinemia. All mutations reported in WHIM patients lead to the truncations in the C-terminal domain of CXCR4, R334X being the most frequent. This defect prevents receptor internalization and enhances both calciu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 53 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…The "warts, hypogammaglobulinemia, infections, and myelokathexis" syndrome is an inherited immune disorder caused by an autosomal dominant heterozygous mutation in CXCR4. Kumar et al (2023) recently found reduced GPCR signaling despite impaired internalization and β-arrestin recruitment in patients carrying a CXCR4Leu317fsX3 mutation causing warts, hypogammaglobulinemia, infections, and myelokathexis syndrome. Our data show that in the presence of ADAM19, lesser amount of β-arrestin2 are recruited with PTHrP, compared to the effects of PTH.…”
Section: Discussionmentioning
confidence: 99%
“…The "warts, hypogammaglobulinemia, infections, and myelokathexis" syndrome is an inherited immune disorder caused by an autosomal dominant heterozygous mutation in CXCR4. Kumar et al (2023) recently found reduced GPCR signaling despite impaired internalization and β-arrestin recruitment in patients carrying a CXCR4Leu317fsX3 mutation causing warts, hypogammaglobulinemia, infections, and myelokathexis syndrome. Our data show that in the presence of ADAM19, lesser amount of β-arrestin2 are recruited with PTHrP, compared to the effects of PTH.…”
Section: Discussionmentioning
confidence: 99%
“…In all investigated variants, critical phospho-acceptor serine/threonine sites needed for G protein-coupled receptor kinase-mediated phosphorylation are removed and this accounts for the failure of CXCR4 to be desensitized and internalized. These deregulations contribute, together with abnormal b-arrestin-dependent signaling, to enhanced CXCL12-promoted chemotaxis in all investigated variants at the exception of the newly described CXCR4 Leu371fsX3 mutation(59,60). A recent genotypephenotype correlation study including 14 WS-associated CXCR4 mutations reported a strong correlation between the degree of internalization defect with the severity of the leukopenia and the recurrence of infections in WS patients(61).…”
mentioning
confidence: 88%
“…However, in vivo treatment with Rapamycin did not correct the circulating lymphopenia in mutant mice despite normalizing the number of MPP4 in the BM and restoring their lymphoid potential in vitro, suggesting that mechanisms underlying the lymphoid rescue in AMD3100-treated mice might be multifactorial and could involve mobilization of lymphoid cells from peripheral tissues and/or modulation of cytokine production by BM stromal cells. Accordingly, Zehentmeier et al recently reported that daily To date, 29 pathogenic CXCR4 variants have been identified in WS patients including nonsense, missense and frameshift mutations(58,59). All of them are positioned in the intracellular region of the C-terminal domain of CXCR4.…”
mentioning
confidence: 99%
“…Periodontitis has been described as a manifestation of WHIM syndrome, although current evidence linking WHIM syndrome and periodontal disease is limited to self-reported patient dental histories within isolated case reports (Aprikyan et al, 2000;Gorlin et al, 2000;Kumar et al, 2023;Mentzer et al, 1977). Sparse information is also present on the possible mechanisms connecting WHIM syndrome with periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils are critical regulators of periodontal health, and disorders affecting neutrophil number (i.e., congenital neutropenia) or recruitment (e.g., leukocyte adhesion deficiency) are associated with severe periodontitis (Moutsopoulos et al, 2014; Silva et al, 2019). Periodontitis has been described as a manifestation of WHIM syndrome, although current evidence linking WHIM syndrome and periodontal disease is limited to self‐reported patient dental histories within isolated case reports (Aprikyan et al, 2000; Gorlin et al, 2000; Kumar et al, 2023; Mentzer et al, 1977). Sparse information is also present on the possible mechanisms connecting WHIM syndrome with periodontal disease.…”
Section: Introductionmentioning
confidence: 99%